2016
DOI: 10.1111/1752-1688.12393
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in the Spatial Distribution of Impervious Cover Relative to Stream Location

Abstract: Use of impervious cover is transitioning from an indicator of surface water condition to one that also guides and informs watershed planning and management, including Clean Water Act (33 U.S.C. §1251 et seq.) reporting. Whether it is for understanding surface water condition or planning and management, impervious cover is most commonly expressed as summary measurement (e.g., percentage watershed in impervious cover). We use the National Land Cover Database to estimate impervious cover in the vicinity of surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…As efficient transporters of water, the dominant function of stormwater drains is to export water and materials that fall on catchment impervious surfaces, independent of their position in a catchment (cf. Wickham et al, 2016). This is in stark contrast to the hydraulically inefficient flow paths in natural catchments, where organic matter deposited within the catchment is likely to be retained and become incorporated into the soil.…”
Section: Are Drains Functioning Ecosystems or Conduits Of Degradation?mentioning
confidence: 96%
See 2 more Smart Citations
“…As efficient transporters of water, the dominant function of stormwater drains is to export water and materials that fall on catchment impervious surfaces, independent of their position in a catchment (cf. Wickham et al, 2016). This is in stark contrast to the hydraulically inefficient flow paths in natural catchments, where organic matter deposited within the catchment is likely to be retained and become incorporated into the soil.…”
Section: Are Drains Functioning Ecosystems or Conduits Of Degradation?mentioning
confidence: 96%
“…In fact, Walsh and Kunapo (2009) found that distance to the nearest stormwater drain was a stronger determinant than distance to the nearest stream. Estimation of distances of impervious surfaces to stormwater drains, which is likely to be a good predictor of whether they are connected to a drain, would certainly produce markedly different conclusions to those of Wickham et al (2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation